Ferritic Stainless Steel Sheet

A ferritic stainless steel plate with controlled composition and carbonitride morphology addresses heat resistance, corrosion resistance, and workability issues, ensuring suitability for both upstream and downstream exhaust members with reduced alloy costs.

JP7603504B2Active Publication Date: 2024-12-20NIPPON STEEL CORPORATION
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2021053999
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-26
Publication Date
2024-12-20
Estimated Expiration
2041-03-26

AI Technical Summary

Technical Problem

Existing ferritic stainless steels used in automobile exhaust members face challenges in providing adequate heat resistance, corrosion resistance, and workability, particularly in complex shapes, with issues such as reduced manufacturability due to high alloy costs and insufficient consideration of ridging during press molding.

Method used

A ferritic stainless steel plate with controlled chemical composition and microstructure, including specific ranges of elements like Ti, Cu, and Nb, and the formation of Ti- and Nb-containing carbonitrides, which enhance heat resistance, corrosion resistance, and workability by suppressing the formation of Cu precipitates and controlling carbonitride morphology.

Benefits of technology

The steel plate achieves good heat resistance, workability, and corrosion resistance, suitable for both upstream and downstream exhaust members, while reducing the need for expensive elements like Nb, thus being economically viable and suitable for complex part fabrication.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007603504000004
    Figure 0007603504000004
  • Figure 0007603504000005
    Figure 0007603504000005
  • Figure 0007603504000001
    Figure 0007603504000001
Patent Text Reader

Abstract

To provide a ferritic stainless steel sheet having good heat resistance, workability and corrosion resistance while reducing Nb.SOLUTION: To provide a ferritic stainless steel sheet which has a chemical composition comprising, by mass%, 0.002 to 0.03% of C, 0.10 to 0.80% of Si, 1.0% or less of Mn, 0.04% or less of P, 0.030% or less of S, 17.0 to 19.5% of Cr, more than 0.60% and 2.0% or less of Mo, 0.05 to 0.20% of Nb, 5×(C+N) to 0.6% of Ti, 0.8 to 2.0% of Cu, 0.002 to 0.03% of N and the balance Fe with inevitable impurities and contains Ti-containing carbonitrides, Nb-containing carbonitrides formed so as to contact with the Ti-containing carbonitrides and has a carbonitride having a cross-sectional area of 1 μm2 or more and the number density of carbonitrides is 5 pieces / mm2 or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a ferritic stainless steel sheet. [Background technology]

[0002] Ferritic stainless steel is used for automobile exhaust components. Such automobile exhaust components are classified into upstream exhaust components and downstream exhaust components. The upstream exhaust components are exposed to high-temperature exhaust gases similar to those discharged from the engine. On the other hand, the downstream exhaust components are also exposed to condensed water and corrosion products such as snow-melting salts that are generated inside the exhaust gases as they are cooled.

[0003] Therefore, because the properties required for the upstream exhaust members and the downstream exhaust members are different, different types of ferritic stainless steels have been used. For example, the upstream exhaust members are exposed to high-temperature exhaust gas, so high-temperature properties are of primary importance. Therefore, Patent Documents 1 and 2 disclose ferritic stainless steels that have improved high-temperature properties, such as heat resistance, oxidation resistance, and high-temperature fatigue properties, for use in the upstream exhaust members.

[0004] The ferritic stainless steels disclosed in Patent Documents 1 and 2 are effective in improving high-temperature properties, but have reduced elements such as Nb, which are expensive and reduce manufacturability. However, instead of reducing these elements, they contain Ti, Cu, etc., and control the contents of other elements to improve high-temperature properties, and are also excellent in terms of raw material costs and manufacturability.

[0005] Furthermore, Patent Document 3 discloses a ferritic stainless steel that is anticorrosive and suitable for use in downstream exhaust components, even in environments where condensed water is generated. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2010-248620 A [Patent Document 2] JP 2013-100596 A [Patent Document 3] International Publication No. 2015 / 174048 Summary of the Invention [Problem to be solved by the invention]

[0007] However, the ferritic stainless steels of Patent Documents 1 and 2 are mainly specialized for high-temperature properties, and no consideration has been given to their corrosion resistance when used in downstream exhaust members. As described above, condensed water is generated in downstream exhaust members. Condensed water is generated inside exhaust members when exhaust gas is cooled, and when gasoline is poorly refined and fuel with a high sulfur content is used, as in other countries, it becomes acidic and highly corrosive. For this reason, when considering use in downstream exhaust members, the ferritic stainless steels of Patent Documents 1 and 2 are required to have further improved corrosion resistance.

[0008] On the other hand, the ferritic stainless steel of Patent Document 3 is mainly specialized for corrosion resistance in the downstream portion, and is considered to have insufficient heat resistance when used as an exhaust member in the upstream portion.

[0009] In addition, in recent years, with the increasing complexity of part shapes, materials for exhaust components are required to have good processability regardless of whether they are upstream or downstream. In this regard, Patent Document 1 mentions processability, but does not consider ridging, which is an issue during press molding. For this reason, problems may arise in molding with a large degree of processing, and there is room for improvement in processability. Furthermore, Patent Documents 2 and 3 do not consider the processability itself.

[0010] Considering the above, there is a problem that it is difficult to use existing ferritic stainless steels as exhaust members, regardless of whether they are in the upstream or downstream portions, in terms of their characteristics. And, as in the above document, there is a problem that it is difficult to provide all the characteristics of excellent heat resistance that can be applied even in a thermal environment of 600 to 800°C, good workability, and good corrosion resistance, while reducing elements such as Nb as much as possible to keep alloy costs down.

[0011] An object of the present invention is to solve the above problems and to provide a ferritic stainless steel sheet having good heat resistance, workability and corrosion resistance while reducing the Nb content. [Means for solving the problem]

[0012] The present invention has been made to solve the above problems, and the gist of the present invention is the following ferritic stainless steel sheet.

[0013] (1) Chemical composition, in mass%, C: 0.002-0.03%, Si: 0.1 to 0.8%, Mn: 1.0% or less, P: 0.04% or less, S: 0.030% or less, Cr: 17.0-19.5%, Mo: more than 0.60% and less than 2.0%, Nb: 0.05-0.2%, Ti: 0.6% or less, Cu: 0.8-2.0%, N: 0.002~0.03%, Ni: 0-0.6%, V: 0~0.5%, W: 0-0.5%, Co: 0-0.5%, Zr: 0-0.5%, Al: 0-1.0%, Sn: 0-0.5%, B: 0~0.005%, Ca: 0-0.01%, Mg: 0 to 0.01%, REM: 0~0.01%, The balance is Fe and impurities. The following formula (i) is satisfied: A carbonitride containing Ti and a carbonitride containing Nb formed in contact with the carbonitride containing Ti, the carbonitride having a cross-sectional area of ​​1 μm 2 The carbonitride is as above. The number density of the carbonitrides is 5 / mm 2 The above is a ferritic stainless steel sheet. 5 × (C + N) ≦ Ti (i) In the above formula, each element symbol represents the content (mass%) of each element contained in the steel, and when no element is contained, the value is set to zero.

[0014] (2) The chemical composition is, in mass%, Ni: 0.01 to 0.6%, V: 0.01-0.5%, W: 0.05~0.5%, Co: 0.01-0.5%, Zr: 0.01-0.5%, Al: 0.01 to 1.0%, and Sn: 0.01-0.5%, The ferritic stainless steel sheet according to the above (1), comprising one or more selected from the following:

[0015] (3) The chemical composition is, in mass%, B: 0.0002~0.005%, Ca: 0.0002-0.01%, Mg: 0.0002 to 0.01%, and REM: 0.0002~0.01%, The ferritic stainless steel sheet according to the above (1) or (2), comprising one or more selected from the following: Effect of the Invention

[0016] According to the present invention, a ferritic stainless steel sheet having good heat resistance, workability and corrosion resistance can be obtained while reducing the Nb content. [Brief description of the drawings]

[0017] [Figure 1] FIG. 1 is a structural photograph showing an example of a Ti-containing carbonitride and a Nb-containing carbonitride (complex carbonitride) formed around the Ti-containing carbonitride. [Diagram 2] FIG. 2 is a diagram showing a schematic example of a structure (complex carbonitride) in which a Ti-containing carbonitride and a Nb-containing carbonitride are formed around the Ti-containing carbonitride. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] The present inventors have investigated the chemical composition of ferritic stainless steel sheets and the above-mentioned characteristics, and have obtained the following findings (a) to (c).

[0019] (a) In order to reduce the cost of raw materials, it is necessary to reduce the amount of expensive elements such as Nb and Mo as much as possible. On the other hand, Nb has the effect of improving heat resistance. In addition to heat resistance, Mo has the effect of improving corrosion resistance even in a condensed water environment that contains sulfur. Therefore, while reducing Nb, heat resistance is ensured by including Cu and Ti. At the same time, corrosion resistance is ensured by adjusting the above-mentioned Cu, Mo, and Cr to an appropriate range. In particular, Cu and Mo contain a lot of sulfur, i.e., SO3 2- This is because it is effective in improving corrosion resistance in a highly concentrated condensed water environment.

[0020] (b) However, the inclusion of elements such as Cu and Ti reduces workability and toughness. The reduction in workability is due to the increase in strength at room temperature caused by the formation of Cu precipitates in the temperature range of 600 to 800°C. The reduction in toughness is due to the precipitation of hard carbonitrides containing Ti (hereinafter simply referred to as "Ti-containing precipitates").

[0021] Therefore, the present inventors have investigated whether the formation of Cu precipitates can be suppressed, and have found that it is effective to add a small amount of Nb within a range in which Nb does not precipitate as a Laves phase that reduces workability and toughness.

[0022] (c) The present inventors also found that the decrease in toughness due to the formation of Ti-containing carbonitrides can be suppressed by controlling the morphology of the carbonitrides. Specifically, the Ti-containing carbonitrides are formed in a polygonal shape, and it is desirable to control the morphology so that Nb-containing carbonitrides (hereinafter simply referred to as "Nb-containing carbonitrides") precipitate in contact with the periphery of the angular parts of the shape.

[0023] The mechanism by which such a carbonitride morphology suppresses the decrease in toughness is unclear. However, in general, strain is likely to accumulate in the polygonal angular parts of Ti-containing carbonitrides, which are likely to become the starting point of cracks. For this reason, it is believed that the above-mentioned morphology changes the state of strain accumulation around the carbonitrides, making it less likely for stress concentration to occur.

[0024] In addition, when hot rolling or cold rolling is performed in a state where the carbonitrides in the above-mentioned form are precipitated, the rolled elongated structure is divided by the strain field around the precipitates. As a result, the formation of the elongated structure can be suppressed, and the occurrence of ridging can also be suppressed. Therefore, it is possible to provide good workability that can be applied even when the degree of processing is large.

[0025] The present invention has been made based on the above findings. Each aspect of the present embodiment will now be described in detail.

[0026] 1.Chemical composition The reasons for limiting the content of each element are as follows. In the following description, "%" for the content means "mass %."

[0027] C: 0.002 to 0.03% In the steel plate according to the present embodiment, Nb-containing carbonitrides are precipitated around Ti-containing carbonitrides, thereby improving toughness. For this reason, it is necessary to contain a certain amount of C or more, and the C content is set to 0.002% or more. However, excessive C content reduces workability and corrosion resistance. It also reduces heat resistance. For this reason, the C content is set to 0.03% or less. From the viewpoint of refining costs, the C content is preferably set to a range of 0.003 to 0.02%, and more preferably to a range of 0.003 to 0.015%.

[0028] Silicon: 0.1 to 0.8% Silicon is an element useful as a deoxidizer and also improves oxidation resistance. Therefore, the silicon content is set to 0.1% or more. However, excessive silicon content reduces ductility at room temperature and reduces workability. Therefore, the silicon content is set to 0.8% or less. The silicon content is preferably set to a range of 0.1 to 0.6%.

[0029] Mn: 1.0% or less Mn is an element useful as a deoxidizer, and also contributes to improving scale adhesion by forming Mn-based oxides on the surface during long-term use. As a result, oxidation resistance is improved. For this reason, Mn may be contained as necessary. However, excessive Mn content not only significantly increases the oxidation weight gain, but also makes it easier for austenite phase to form at high temperatures. As a result, heat resistance is reduced. Therefore, the Mn content is set to 1.0% or less. On the other hand, in order to obtain the above effects, the Mn content is preferably 0.1% or more. The Mn content is preferably in the range of 0.2 to 0.8%.

[0030] P:0.04% or less P is a harmful element that reduces toughness and workability. Therefore, the P content is set to 0.04% or less. The P content is preferably set to 0.03% or less. It is preferable to reduce P as much as possible, but excessive reduction of P increases refining costs. Therefore, the P content is preferably set to 0.01% or more.

[0031] S: 0.030% or less S is an element that reduces elongation, adversely affects workability, and reduces corrosion resistance. Therefore, the S content is set to 0.030% or less. The S content is preferably set to 0.010% or less, and more preferably set to 0.005% or less. It is preferable to reduce S as much as possible, but excessive reduction of S increases refining costs. Therefore, the S content is preferably set to 0.0003% or more.

[0032] Cr: 17.0~19.5% Cr is an element effective in improving the corrosion resistance and oxidation resistance, which are characteristics of stainless steel. If the Cr content is less than 17.0%, the Cr fraction in the passive film is insufficient, and in addition to not being able to obtain corrosion resistance, the oxidation resistance required for long-term use at about 800°C is not obtained. For this reason, the Cr content is set to 17.0% or more. However, if Cr is contained in excess, the steel is solid-solution strengthened at room temperature, hardened, and has low ductility, thereby decreasing workability. In particular, if the Cr content exceeds 19.5%, the adverse effects on the above properties become significant, so the Cr content is set to 19.5% or less. The Cr content is preferably set to a range of 17.5 to 19.0%.

[0033] Mo: more than 0.60% and less than 2.0% Mo has the effect of improving heat resistance, oxidation resistance, and corrosion resistance. In particular, SO3 2- When the concentration is high, it is necessary to add Cu in combination with Mo to ensure adequate corrosion resistance, and the Mo content is set to more than 0.60%. However, if Mo is added in excess, the steel is hardened by solid solution strengthening, which reduces workability. In addition, Mo is an expensive element, which increases the alloy cost. For this reason, the Mo content is set to 2.0% or less. The Mo content is preferably set to 1.5% or less, and more preferably set to 1.0% or less.

[0034] Nb: 0.05~0.2 Nb has the effect of improving high-temperature strength and thermal fatigue properties. In addition, the inclusion of Nb suppresses the formation of Cu precipitates at high temperatures. Furthermore, by precipitating Nb-containing carbonitrides so as to be in contact with the periphery of Ti-containing carbonitrides, it has the effect of increasing toughness and suppressing the recovery of strain introduced during hot rolling. For this reason, the Nb content is set to 0.05% or more. The Nb content is preferably set to 0.06% or more. However, if an excessive amount of Nb is included, a Laves phase containing Nb is formed, and the toughness and workability are reduced. For this reason, the Nb content is set to 0.2% or less. The Nb content is preferably set to 0.18% or less.

[0035] Ti: 0.6% or less In the steel sheet of this embodiment, the Nb content is reduced. Therefore, Ti is an important element in fixing C and N. Ti has the effect of fixing C and N, suppressing the occurrence of sensitization, and improving corrosion resistance, intergranular corrosion resistance and oxidation resistance of welded parts. In addition, by forming Nb-containing carbonitrides around the Ti-containing carbonitrides precipitated by fixing C and N, the surroundings of the carbonitrides become the source of strain fields during hot rolling and cold rolling, and the rolled elongated structure is divided. As a result, the occurrence of ridging is suppressed and the workability is improved. For this reason, the Ti content needs to satisfy the following formula (i).

[0036] 5 × (C + N) ≦ Ti (i) In the above formula, each element symbol represents the content (mass%) of each element contained in the steel, and when no element is contained, the value is set to zero.

[0037] However, excessive Ti content reduces toughness and induces surface defects. Therefore, the Ti content is set to 0.6% or less. Although it depends on the C and N contents, the Ti content is preferably set to the range of 0.15 to 0.4%, and more preferably to the range of 0.2 to 0.3%.

[0038] Cu: 0.8-2.0% As described above, Cu is an element effective for improving heat resistance in the temperature range of about 600 to 800°C. It is also an element effective for improving sulfuric acid resistance. In this embodiment, Nb, which is effective for improving high-temperature strength, is reduced, and SO3 2- Even when the concentration is high, it is necessary to ensure corrosion resistance. For this reason, Cu is included together with Mo. In this case, the Cu content is set to 0.8% or more. The Cu content is preferably set to 1.0% or more, and more preferably set to 1.1% or more. However, excessive Cu content not only reduces oxidation resistance and workability, but also promotes coarsening of Cu precipitates (also called "ε-Cu"). For this reason, the Cu content is set to 2.0% or less. The Cu content is preferably set to 1.5% or less.

[0039] N: 0.002~0.03% N forms coarse and hard TiN at high temperatures, and is generated in the strain field around precipitates during hot rolling, thereby dividing the rolled elongated structure and improving workability. For this reason, the N content is set to 0.002% or more. However, excessive N content, like C, reduces workability and corrosion resistance, and also reduces heat resistance. For this reason, the N content is set to 0.03% or less. In consideration of the refining cost, the N content is preferably set to a range of 0.003 to 0.02%, and more preferably set to a range of 0.003 to 0.015%.

[0040] In addition to the above elements, one or more elements selected from Ni, V, W, Co, Zr, Al and Sn may be contained within the ranges shown below. The reasons for limiting each element will be explained.

[0041] Ni: 0-0.6% Ni is an element that improves the toughness of ferritic stainless steel and suppresses the occurrence of cracks. Therefore, it may be contained as necessary. However, since Ni is a strong austenite phase generating element, if it is contained in excess, it makes it easier to generate austenite phase at high temperatures and reduces heat resistance. In addition, since Ni is an expensive element, the alloy cost also increases. Therefore, the Ni content is set to 0.6% or less. The Ni content is preferably set to 0.5% or less, and more preferably set to 0.3% or less. On the other hand, in order to obtain the above effect, the Ni content is preferably set to 0.01% or more.

[0042] V: 0 to 0.5% V, like Nb and Ti, is a carbonitride-forming element, and has the effect of improving heat resistance by finely precipitating these carbonitrides. Therefore, it may be contained as necessary. However, excessive V content leads to deterioration of manufacturability. Therefore, the V content is set to 0.5% or less. The V content is preferably set to 0.4% or less, and more preferably set to 0.3% or less. On the other hand, in order to obtain the above effect, the V content is preferably set to 0.01% or more.

[0043] W: 0~0.5% W has the effect of increasing heat resistance. Therefore, it may be contained as necessary. However, excessive W content promotes the formation of intermetallic compounds and reduces the toughness and workability of the steel. Therefore, the W content is set to 0.5% or less. The W content is preferably set to 0.4% or less, and more preferably set to 0.3% or less. On the other hand, in order to obtain the above effect, the W content is preferably set to 0.05% or more, and more preferably set to 0.1% or more.

[0044] Cobalt: 0-0.5% Co has the effect of improving heat resistance and lowering the thermal expansion coefficient. Therefore, it may be contained as necessary. However, excessive Co content hardens the steel by solid solution strengthening, which reduces workability. In addition, Co is an expensive element, so the alloy cost increases. Therefore, the Co content is set to 0.5% or less. The Co content is preferably set to 0.4% or less, and more preferably set to 0.3% or less. On the other hand, in order to obtain the above effect, the Co content is preferably set to 0.01% or more.

[0045] Zr: 0-0.5% Zr has the effect of improving oxidation resistance. Therefore, it may be contained as necessary. However, excessive Zr content generates intermetallic compounds and reduces the toughness and workability of the steel. Therefore, the Zr content is set to 0.5% or less. The Zr content is preferably set to 0.4% or less, and more preferably set to 0.3% or less. On the other hand, in order to obtain the above effect, the Zr content is preferably set to 0.01% or more.

[0046] Al: 0-1.0% Al is used as a deoxidizer and also has the effect of improving oxidation resistance. Therefore, it may be contained as necessary. However, excessive Al content hardens the steel through solid solution strengthening, and reduces the toughness and workability of the steel. Therefore, the Al content is set to 1.0% or less. The Al content is preferably set to 0.6% or less, and more preferably set to 0.2% or less. On the other hand, in order to obtain the above effect, the Al content is preferably set to 0.01% or more.

[0047] Sn: 0-0.5% Sn has the effect of improving corrosion resistance without significantly deteriorating mechanical properties at room temperature. Therefore, it may be contained as necessary. However, excessive Sn content significantly reduces manufacturability. Therefore, the Sn content is set to 0.5% or less. The Sn content is preferably set to 0.3% or less, and more preferably set to 0.2% or less. On the other hand, in order to obtain the above effect, the Sn content is preferably set to 0.01% or more.

[0048] In addition to the above elements, one or more elements selected from B, Ca, Mg and REM may be contained within the ranges shown below. The reasons for limiting each element will be explained below.

[0049] B: 0~0.005% B has the effect of improving workability, particularly secondary workability. Therefore, it may be contained as necessary. However, excessive B content reduces weldability and toughness. Therefore, the B content is set to 0.005% or less. The B content is preferably set to 0.003% or less, and more preferably set to 0.0015% or less. On the other hand, in order to obtain the above effect, the B content is preferably set to 0.0002% or more.

[0050] Ca: 0 to 0.01% Ca has the effect of preventing nozzle clogging, which is likely to occur during continuous casting. Therefore, it may be contained as necessary. However, excessive Ca content makes surface defects more likely to occur. Therefore, the Ca content is set to 0.01% or less. The Ca content is preferably set to 0.005% or less, and more preferably set to 0.003% or less. On the other hand, in order to obtain the above effect, the Ca content is preferably set to 0.0002% or more.

[0051] Magnesium: 0 to 0.01% Mg has the effect of increasing the equiaxed crystal ratio of the slab and improving toughness and workability. Therefore, Mg may be contained as necessary. However, excessive Mg content reduces the toughness of the steel and deteriorates the surface properties. Therefore, the Mg content is set to 0.01% or less. The Mg content is preferably set to 0.005% or less, and more preferably set to 0.003% or less. On the other hand, in order to obtain the above effects, the Mg content is preferably set to 0.0002% or more.

[0052] REM: 0~0.01% REM (rare earth elements) have the effect of improving oxidation resistance. Therefore, they may be contained as necessary. However, excessive REM content reduces weldability and toughness. Therefore, the REM content is set to 0.01% or less. The REM content is preferably set to 0.008% or less, and more preferably set to 0.005% or less. On the other hand, in order to obtain the above effect, the REM content is preferably set to 0.0002% or more.

[0053] REM refers to a total of 17 elements, including Sc, Y and lanthanides, and the above REM content refers to the total content of these elements. In industry, REM is often added in the form of misch metal.

[0054] In the chemical composition of the present invention, the balance is Fe and impurities. Here, the term "impurities" refers to The term "compounds" refers to components that are mixed in during industrial steel production due to various factors in raw materials such as ores and scraps, and in the production process, and that are acceptable within a range that does not adversely affect the present invention.

[0055] 2. Carbonitride The steel sheet according to the present embodiment is a steel sheet in which carbonitrides are dispersed and precipitated in a matrix. The steel sheet has carbonitrides including Ti-containing carbonitrides containing Ti and Nb-containing carbonitrides containing Nb. The carbonitrides described above have a cross-sectional area of ​​1 μm 2 Here, the carbonitride refers to a compound containing C and / or N, and the above-mentioned cross-sectional area refers to the area of ​​the carbonitride observed when the structure is observed by the method described later, that is, the area when the observation surface is projected horizontally.

[0056] The Ti-containing carbonitride contained in the carbonitride described above has high compatibility with the matrix, and has a polygonal shape as shown in the center of FIG. 1, and is relatively coarse in size. It is also a hard compound. In particular, strain is likely to accumulate in the polygonal angular parts of the hard Ti-containing carbonitride, and it is likely to become the starting point of fracture. As a result, cracks propagate, the toughness decreases, and it becomes difficult to ensure the reduction rate in cold rolling due to this. In addition, it becomes difficult to improve the workability, especially the r-value.

[0057] For this reason, as shown in Fig. 1 and Fig. 2, the Nb-containing carbonitride is formed later so as to be in contact with the periphery of the angular portion of the Ti-containing carbonitride, that is, the Nb-containing carbonitride needs to be formed so as to be in contact with the periphery of the Ti-containing carbonitride. This is because it is considered that the radius of curvature of the overall shape of the carbonitride becomes large, and the occurrence of stress concentration is suppressed. In this case, it is sufficient that the Nb-containing carbonitride is formed in a part of the periphery of the Ti-containing carbonitride, and it is particularly preferable that the Nb-containing carbonitride is formed around the angular portion of the Ti-containing carbonitride, and it is preferable that the Nb-containing carbonitride is formed continuously at a plurality of locations.

[0058] The Ti-containing carbonitride may be, for example, TiN, TiC, etc. The Nb-containing carbonitride may be, for example, NbC, NbN, etc.

[0059] The carbonitride includes the above carbonitride, i.e., a Ti-containing carbonitride and a Nb-containing carbonitride formed in contact with the Ti-containing carbonitride, and has a cross-sectional area of ​​1 μm 2 The number density of the carbonitrides having the above properties (hereinafter, for simplicity, also referred to as "composite carbonitrides") is 5 pieces / mm 2 The density of composite carbonitride particles is 5 particles / mm 2 If the density is less than 5 / mm, there will be many crack starting points, making it difficult to obtain good toughness and workability. 2 The density of the composite carbonitride particles is 10 particles / mm 2 More preferably, it should be 15 pieces / mm 2It is more preferable that the number density of the complex carbonitrides is equal to or higher than this value.

[0060] As described above, Cu precipitates finely precipitate in the temperature range of 600 to 800 ° C, increase the high-temperature strength of the steel sheet in the temperature range of the usage environment, and dissolve at higher temperatures. On the other hand, by adding a small amount of Nb in a range in which the Laves phase does not precipitate, the growth of Cu precipitates when held in the temperature range of 600 to 800 ° C is suppressed, the precipitation of Cu precipitates during the cooling process from the solid solution state is suppressed, and the decrease in toughness due to the improvement of the room temperature strength of the steel sheet is suppressed. In addition, by forming a complex carbonitride with a controlled morphology as described above, when the precipitation sites of Cu precipitates are reduced, it is possible that Cu precipitation itself can also be suppressed.

[0061] The measurement of complex carbonitrides may be performed by the following procedure. Specifically, an observation sample is taken from the left side of the steel sheet. This observation sample is applied with a potential of -100mV to 400mV against a saturated calomel reference electrode (SCE) in a non-aqueous electrolyte solution consisting of 10 mass% acetylacetone, 1 mass% tetramethylammonium chloride, and 89 mass% methyl alcohol. This dissolves the matrix (metal base) of the sample, making it possible to distinguish between the matrix and compounds such as carbonitrides, and the metal structure is observed with an SEM. During the observation, the magnification is set to 5000 times, and the number of fields of view is set to 100.

[0062] Then, the carbonitride is observed, and the composition of the carbonitride that is thought to be a coarse Ti-containing carbonitride is analyzed by EDX attached to the SEM as shown in FIG. 1, and the composition is confirmed and it is judged whether it is a Ti-containing carbonitride. Similarly, the composition of the carbonitride formed in contact with the coarse carbonitride is also confirmed and it is judged whether it is a Nb-containing carbonitride. At this time, the cross-sectional area of ​​the entire carbonitride is measured and it is judged whether it is a composite carbonitride. The cross-sectional area is calculated by multiplying the major axis of the observed composite carbonitride by the minor axis. The major axis is the length of the longest straight line among the straight lines connecting two points on the periphery in the horizontal or vertical direction, and the minor axis is the length of the shortest straight line among the straight lines connecting two points on the periphery in the horizontal or vertical direction. The number density may be calculated by counting the number of composite carbonitrides observed at the above magnification and number of fields of view, and dividing by the area of ​​the observation field of view.

[0063] 3. Manufacturing method A preferred method for manufacturing the steel sheet according to the present embodiment will be described. The steel sheet according to the present embodiment can obtain the effects as long as it has the above-mentioned configuration regardless of the manufacturing method, but can be stably manufactured, for example, by the following manufacturing method. In the following description, the case of a cold-rolled annealed sheet will be described.

[0064] A steel having the above chemical composition is melted and a slab is produced by a conventional method. The resulting slab is heated and hot-rolled. The heating temperature of the slab is not particularly limited, but is usually in the range of 1150 to 1250°C.

[0065] In addition, during hot rolling, the steel is allowed to dwell for 1 minute or more in a temperature range of 900 to 1100°C. If the dwell time in the above temperature range is less than 1 minute, complex carbonitrides are difficult to form, and the number density of complex carbonitrides decreases. As a result, it becomes difficult to obtain the effect of improving toughness and workability. For this reason, the dwell time in the above temperature range is set to 1 minute or more, and preferably 1.5 minutes or more. The upper limit of the dwell time in the above temperature range is not particularly limited, but is usually set to 4 minutes or less from the viewpoint of manufacturability.

[0066] The hot rolling completion temperature is usually about 850 to 950°C. Thereafter, hot-rolled sheet annealing is performed as necessary. When hot-rolled sheet annealing is performed, the conditions are not particularly limited, but for example, annealing may be performed for 2 minutes or less at an annealing temperature in the range of 900 to 1050°C. Whether hot-rolled sheet annealing is performed or not, it is preferable to set the average cooling rate in the temperature range of 800 to 400°C to 10°C / s or more. If the average cooling rate in the temperature range of 800 to 400°C is less than 10°C / s, Cu precipitates will precipitate when passing through the temperature range. For this reason, the average cooling rate in the temperature range is preferably 10°C / s or more. For example, pickling may be performed as necessary after hot rolling and after hot-rolled sheet annealing.

[0067] The obtained hot-rolled sheet (or hot-rolled annealed sheet) is cold-rolled to obtain a cold-rolled sheet. The rolling reduction during cold rolling may be adjusted as necessary. The obtained cold-rolled sheet is annealed as necessary. The annealing temperature of the cold-rolled sheet annealing is preferably 950° C. or less.

[0068] If the annealing temperature in the cold-rolled sheet annealing exceeds 950°C, the crystal grains become coarse, and rough surfaces occur after processing. In addition, the fuel cost required for annealing increases, and the load in the pickling process also increases. For this reason, the annealing temperature in the cold-rolled sheet annealing is preferably 950°C or less. The annealing time in the cold-rolled sheet annealing is not particularly limited, but from the viewpoint of manufacturability, it is considered that it is usually within 2 minutes.

[0069] In addition, in the cooling during annealing of the cold-rolled sheet, it is preferable to set the average cooling rate to 10°C / s or more in the temperature range of 800 to 400°C. This is because it is possible to suppress the formation of Cu precipitates. In addition, for example, pickling may be performed as necessary after cold rolling and after annealing of the cold-rolled sheet.

[0070] The steel sheet of this embodiment will be described more specifically with reference to the following examples, but the present invention is not limited to these examples. EXAMPLES

[0071] Steels having the chemical compositions shown in Table 1 were melted by vacuum melting, cast into a mold with a thickness of 80 mm, heated at 1230°C for 2 hours, and hot rolled to obtain hot-rolled sheets with a thickness of 5 mm. At this time, the residence time in the temperature range of 900°C to 1100°C was controlled. Note that the hot rolling speed was adjusted so that the residence time in the temperature range of 900°C to 1100°C was less than 1 minute only for Steel 13 and Steel 14, and the residence time in the above temperature range for the other steels was set to 1 minute or more. In addition, the cooling rate and other conditions were adjusted so as to be within the range of the above-mentioned preferable conditions.

[0072] Next, the hot-rolled sheet was pickled and then cold-rolled to a thickness of 1.5 mm to obtain a cold-rolled sheet. The cold-rolled sheet was then annealed at 920°C, which satisfies the above-mentioned preferable conditions, and then pickled to obtain a cold-rolled annealed sheet. In the above examples, the average cooling rate in the temperature range of 800 to 400°C was always 10°C / s or more.

[0073] [Table 1]

[0074] From the viewpoint of manufacturability, the toughness of the hot-rolled sheet before cold rolling was also evaluated by the method described later. In addition, the morphology of carbonitrides in the obtained cold-rolled annealed sheet was observed by the method described later. Then, the heat resistance, workability, and corrosion resistance were evaluated by the methods described later.

[0075] (Hot-rolled sheet toughness) The toughness of the hot-rolled sheet was measured as an index for evaluating manufacturability. V-notch sub-size Charpy impact test pieces were prepared from the hot-rolled sheet with the same sheet thickness as the hot-rolled sheet so that the longitudinal direction of the test piece was parallel to the rolling direction, and five test pieces were subjected to the test according to the test method described in JIS Z 2242:2018. The impact value was calculated by dividing the measured absorbed energy by the cross-sectional area, and the lowest value among the five was taken as the Charpy impact value. From the viewpoint that the hot-rolled coil can be uncoiled without any problems and manufacturability is good, a Charpy impact value of 30 J / cm was selected.2 The characteristics were evaluated as good when the test temperature was set to room temperature (23±5°C).

[0076] (Carbonitride Form) To investigate the morphology of carbonitrides, an observation sample was taken from the left side of the steel sheet. This observation sample was placed in a non-aqueous electrolyte solution consisting of 10% by mass of acetylacetone, 1% by mass of tetramethylammonium chloride, and 89% by mass of methyl alcohol, and a potential of -100mV to 400mV was applied to the observation sample against a saturated calomel reference electrode (SCE). This dissolved the matrix (metal base) of the sample, making it possible to distinguish between the matrix and compounds such as carbonitrides, and the metal structure was observed with a SEM. During the observation, the magnification was set to 5000 times, and the number of fields of view for measurement was set to 100.

[0077] Then, the carbonitrides were observed, and the composition of the carbonitrides thought to be coarse Ti-containing carbonitrides was analyzed using EDX attached to the SEM, and the composition was confirmed to determine whether they were Ti-containing carbonitrides. Similarly, the composition of the carbonitrides formed in contact with the coarse carbonitrides was also confirmed to determine whether they were Nb-containing carbonitrides. At this time, the cross-sectional area of ​​the entire carbonitride was measured to determine whether it was a composite carbonitride. The cross-sectional area was calculated by multiplying the major axis of the observed composite carbonitride by the minor axis. The number density was calculated by counting the number of composite carbonitrides observed at the above magnification and number of fields of view, and dividing by the area of ​​the observation field of view.

[0078] (Heat resistance) Test pieces were taken from the obtained cold-rolled annealed sheets, and a high-temperature tensile test was performed at 800°C to measure the 0.2% yield strength. The tensile test was performed in accordance with JIS G 0567:2012, and a test piece having an 800°C yield strength of 25 MPa or more was evaluated as having good heat resistance.

[0079] (processability) Workability was evaluated by measuring the total elongation (elongation at break) and the waviness height, which is an index of ridging resistance. Total elongation was measured in accordance with JIS Z 2201:1998 by taking JIS No. 13B test pieces from the cold-rolled annealed sheet with the longitudinal direction as the rolling direction. If the total elongation at room temperature is 30% or more, it will be possible to process it into complex parts, so a total elongation of 30% or more was evaluated as a good characteristic value.

[0080] The waviness height was measured by the following procedure. Specifically, a JIS No. 5 tensile test piece was taken from the cold-rolled annealed sheet in which the longitudinal direction was the rolling direction, and a tensile strain was applied until the elongation rate in the parallel part was 20%, and then the load was removed to prepare a test piece. The surface profile of the test piece at the center of the longitudinal direction was measured in the width direction (i.e., the direction perpendicular to the rolling direction), and a waviness curve with wavelength components of 0.5 to 8.0 mm was determined according to JIS B 0601:2013 with cutoff values ​​λf = 8.0 mm and λc = 0.5 mm, and the arithmetic mean waviness Wa (μm) was calculated from the waviness curve, which was defined as the waviness height W. A waviness height W of 2.0 μm or less was evaluated as a good characteristic value.

[0081] (Corrosion resistance) The corrosion resistance was evaluated by carrying out the following boiling condensation test. Specifically, a strip-shaped test piece of 50 mm x 120 mm was cut out from the obtained cold-rolled annealed sheet. Next, the test piece was immersed in the test liquid shown in Table 2 in a semi-immersed state to simulate an environment in which exhaust gas condensation and evaporation are repeated, and boiled for 4 hours to concentrate it to 6 times, and then held for 20 hours under condensation conditions of a temperature of 30 ° C and a relative humidity of 80%. This was repeated five times, and a cycle of heating at 400 ° C for 2 hours was repeated twice to simulate heating by exhaust gas. The test liquid shown in Table 2 was created with reference to an analysis example of condensed water generated when using fuel with a high S concentration, and the test liquid was adjusted with ammonium salt in all cases. After the test, the rust was removed and the maximum erosion depth was measured, and a maximum erosion depth of 0.4 mm or less was evaluated as a good characteristic value. The results are summarized in Table 3.

[0082] [Table 2]

[0083] [Table 3]

[0084] The cold-rolled annealed sheets of steels 1 to 12 met the requirements for composition and complex carbonitrides, so all the results of heat resistance, corrosion resistance, and workability were good. On the other hand, although the composition of steel 13 was satisfactory, the number density of complex carbonitrides was low and workability was insufficient because it was not manufactured under favorable manufacturing conditions. In addition, the toughness of the hot-rolled sheet was also reduced. Steels 14 to 17 are assumed to be ferritic stainless steel sheets conventionally used in the upstream part of the exhaust gas path, and although the heat resistance was satisfactory, at least one of the properties of corrosion resistance and workability was poor. In addition, the toughness of the hot-rolled sheet was also reduced. Steels 18 and 19 did not satisfy the ranges of Mo and Cu contents of this embodiment, so the heat resistance and corrosion resistance were poor. In addition, steel 20 did not satisfy the ranges of this embodiment, so the heat resistance was insufficient, complex carbonitrides were not sufficiently formed, and workability was also reduced. In addition, the toughness of the hot-rolled sheet was also reduced. [Industrial Applicability]

[0085] The steel plate of this embodiment can reduce Nb and is economical. In addition, it has heat resistance that can be applied even in a high-temperature environment of 600 to 800°C. In addition, it has good workability and corrosion resistance, so it can be applied to exhaust members regardless of whether they are in the upstream or downstream part. Therefore, the steel plate of this embodiment is suitable as a material for exhaust members. [Explanation of symbols]

[0086] 1.Ti-containing carbonitride 2.Nb-containing carbonitride

Claims

1. The chemical composition, in mass%, is C: 0.002-0.03%, Si: 0.1-0.8%, Mn: 1.0% or less, P: 0.04% or less, S: 0.030% or less, Cr: 17.0-19.5%, Mo: more than 0.60% and less than 2.0%, Nb: 0.05-0.2%, Ti: 0.6% or less, Cu: 0.8-2.0%, N: 0.002-0.03%, Ni: 0 to 0.6%, V: 0 to 0.5%, W: 0 to 0.5%, Co: 0 to 0.5%, Zr: 0 to 0.5%, Al: 0-1.0%, Sn: 0 to 0.5%, B: 0 to 0.005%, Ca: 0-0.01%, Mg: 0 to 0.01%, REM: 0-0.01%, The balance is Fe and impurities. The following formula (i) is satisfied: A titanium-containing carbonitride and a niobium-containing carbonitride formed in contact with the titanium-containing carbonitride, the cross-sectional area of ​​which is 1 μm 2 The carbonitride is as above. The number density of the carbonitrides is 5 pieces / mm 2 The above is a ferritic stainless steel sheet. 5×(C+N)≦Ti...(i) In the above formula, each element symbol represents the content (mass%) of each element contained in the steel, and when no element is contained, the value is set to zero.

2. The chemical composition, in mass%, Ni: 0.01-0.6%, V: 0.01-0.5%, W: 0.05-0.5%, Co: 0.01-0.5%, Zr: 0.01 to 0.5%, Al: 0.01 to 1.0%, and Sn: 0.01-0.5%, The ferritic stainless steel sheet according to claim 1, comprising one or more selected from the following:

3. The chemical composition, in mass%, B: 0.0002 to 0.005%, Ca: 0.0002-0.01%, Mg: 0.0002 to 0.01%, and REM: 0.0002-0.01%, The ferritic stainless steel sheet according to claim 1 or 2, comprising one or more selected from the following:

Citation Information

Patent Citations

  • Ferritic stainless steel sheet having superior ridging resistance, formability and brittleness resistance in secondary forming, and manufacturing method therefor

    JP2005272865A

  • Ferritic stainless sheet sheet and steel tube for bent tube having sectional shape for components

    JP2006274436A

  • Cold rolled ferritic stainless steel sheet excellent in surface distortion resistance and surface property

    JP2007254763A

  • Ferritic cold-rolled stainless steel sheet having excellent workability and method for manufacturing the same

    JP2010235994A

  • Ferritic stainless steel plate excellent in heat resistance and workability

    JP2010248620A